The Relationship between Sport-Confidence and Goal Commitment of Amateur Footballers - Berat Koçyiğit; Aydın Şentürk (Journal of Educational Issues, 2024)
The goal of this study is to examine the relationship between amateur football players’ Sport-confidence and goal commitment. The study consisted of amateur footballers in Isparta province. The sample group consisted of 194 male athletes who played in amateur teams. In this study, the personal information and the sports self-confidence scale and the commitment to team goals scale in the literature were used. Continuous Sport-confidence Scale was developed by Vealey (1986) and adapted to Turkish by Engür et al. (2006).The scale consists of 13 items in total and constitutes a dimension of the Sport-confidence scale. The overall internal consistency coefficient in the adaptation study of the scale was found to be 0.89. Goal Commitment Scale in Sports was developed by Klein vd (2001) and adapted to Turkish by Şenel and Yıldız (2016). The scale, which consists of 5 items and a single sub-dimension, is a five-point Likert-type scale. The overall internal consistency coefficient in the adaptation study of the scale was found to be 0.70. Statistical analysis was performed in computer environment. Pearson correlation analysis (r) was applied. As a result, it was observed that amateur football players participating in the study had high levels of sport-confidence and commitment to team goals. A moderate positive correlation was found between sport-confidence and commitment to team goals. This is thought to be due to the fact that amateur football players want to prove themselves and that the success of the team is also adopted as the success of their football players.